1975
DOI: 10.1084/jem.141.4.904
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the clonal abortion theory of B-lymphocyte tolerance.

Abstract: This paper deals with the behavior of adult mouse bone marrow cells placed in tissue culture with or without antigen, and subsequently assessed for immune competence after adoptive transfer into lethally X- irradiated, syngeneic hosts. Attention was focussed on B lymphocytes through using hapten human gamma globulin (HGG) preparations as putative tolerogens in tissue culture, the T-cell-independent antigens DNP-POL and NIP-POL as challenge injections in adoptive hosts, and numbers of hapten-specific PFC in hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(131 citation statements)
references
References 24 publications
8
123
0
Order By: Relevance
“…Presumably, most of the progenitors that can acquire s-Ig receptors in vitro have done so within the incubation period, and the presence of tolerogen during this maturation phase almost totally eliminates the potential anti-DNP clones. This is consistent with our previous results in which immature B cells in the absence of T cells are highly susceptible to tolerance induction (18,20) and provides strong evidence in favor of the clonal abortion theory (38).…”
Section: Discussionsupporting
confidence: 82%
“…Presumably, most of the progenitors that can acquire s-Ig receptors in vitro have done so within the incubation period, and the presence of tolerogen during this maturation phase almost totally eliminates the potential anti-DNP clones. This is consistent with our previous results in which immature B cells in the absence of T cells are highly susceptible to tolerance induction (18,20) and provides strong evidence in favor of the clonal abortion theory (38).…”
Section: Discussionsupporting
confidence: 82%
“…Nossal and Pike have recently reported that IgM antihaptenforming precursor B-cells in adult mouse bone marrow are much more sensitive to hapten-specific tolerance induced in vitro by deaggregated dinitrophenylhuman gammaglobulin than are similar cells in adult spleen (24). Their observations, together with our own, lend support to the old, but presently unfashionable hypothesis, that tolerance to self, at least in B cells, may be related to B cells passing through a stage in their normal differentiation where they are highly susceptible to tolerance induction (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…These notions, originally proposed by Nossal and Pike [3,4], were apparently supported by in vivo studies in the HEL/anti-HEL transgenic model, where high avidity BCR interactions led to the elimination of HEL-reactive cells in the bone marrow, while low avidity interactions indeed yielded self-reactive cells in the periphery [5]. However, following description of the TR compartment, Fulcher and Basten demonstrated that these 'anergic' B cells achieved entrance to the TR pools, but nonetheless died rapidly before entering mature pools [6].…”
Section: B Cells Undergo Both Negative and Positive Selection As Theymentioning
confidence: 99%